Effect of cutting speed and depth of cut on surface roughness of oil-quench mild steel - Yeong, Choy Huey (2009)
Mild steels are often employed in high volume of screw machine parts such as shafts, spindles, pins, rods and varieties of component parts where high hardness is required. Although mild steel provides various advantages such as ease of formability, machinability and weldability but it is unimpressive in terms of strength and hardness. The most common problem encountered is the short tool life. Hence, the ability to make mild steels hard enough to be the tools that shape all other material is important. Mild steel ability to be hardened is produced in heat treatment and quenching process. Thus, the main objective of this project is to determine the effect of cutting speed and depth of cut on surface roughness of oil-quenched mild steel. Material is prepared by heating mild steel followed by quenching in oil. The hardness of quenched mild steel was tested with Rockwell hardness tester to determine suitable machining parameters. Taguchi and orthogonal array DOE was employed to set up experiments. The surface of oil-quenched mild steel was measured with perthometer and data were collected. Analysis of data obtained were made by using Analysis of Variance (ANOVA), Response Surface Methodology (RSM) and validation test were carried out to determine significant parameter affecting surface quality of specimen studied. Conclusions were then made based on results obtained.